The Effects of Ethnic Conflict on Trading and Marketing Activities in Southern Taraba Senatorial District, Taraba State, Nigeria - Daniel, Rosemary Onchi; Adi, Amos Joyce; Douglas, Audu Stephen (Darul Yasin Al Sys, 2026)
Recurrent ethnic conflicts in Southern Taraba Senatorial District have significantly affected socio-economic stability, prompting this study titled Ethnic Conflict and Trading Activities in Southern Taraba Senatorial District, Taraba State. The research investigates the impact of ethnic conflict on trading and marketing activities, with specific objectives to identify the underlying causes of conflict, assess its effects on trade, and propose strategies for sustainable peace. Grounded in the Frustration–Aggression Theory, the study explains how prolonged deprivation, inequality, and perceived injustice serve as catalysts for violent inter-ethnic confrontations. A descriptive cross-sectional survey design was adopted, involving 400 respondents selected from a population of 1,520,700 across Wukari, Donga, Ibi, Takum, and Ussa Local Government Areas, using the Taro Yamane formula. Data were collected through structured questionnaires and in-depth interviews with key informants, including religious and traditional leaders. Quantitative data were analyzed using descriptive statistics, while qualitative responses underwent thematic interpretation. The findings indicate that ethnic rivalry, political marginalization, resource competition, and poverty are primary drivers of conflict in the region. Ethnic violence has significantly disrupted commercial activities through market destruction, loss of merchandise, trader displacement, and inflation in commodity prices. The study concludes that ethnic conflict poses a major threat to economic sustainability in Southern Taraba. It recommends a shift from reactive conflict resolution to proactive prevention by promoting inclusive governance, institutionalized dialogue, and peace education. Additionally, rehabilitating damaged market infrastructure and providing financial support to displaced traders are essential for economic recovery and long-term peacebuilding in the region.